KECERDASAN EMOSIONAL DAN PENDIDIKAN AGAMA ISLAM (Telaah Atas Pemikiran Darwis Hude) - Salsabilatussa’dyah; akmal (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2024)
Abstract: The purpose of this study is to analyze Darwis Hude's thoughts on emotional intelligence and describe its relevance to the relevance of Islamic Religious Education. This study uses library research and focuses on studying emotional intelligence according to Darwis Hude which is contained in his book Emotions: Religious-Psychological Exploration of Human Emotions in the Qur'an. The analysis technique used is content analysis. The findings of this study are the relevance of emotional intelligence according to Darwis Hude, namely directing educators to understand emotional intelligence that will be able to control facial expressions, voice, attitude and behavior when carrying out the teaching and learning process in the classroom. The deeper a person studies his emotions, the deeper a person's faith. Because he knows that the emotions in him will produce something good if managed properly.